Spatial and temporal variations of CO2 emissions from the active fault zones in the capital area of China. (January 2020) - Chen, Zhi; Li, Ying; Martinelli, Giovanni; Liu, Zhaofei; Lu, Chang; Zhao, Yuanxin
Abstract: The chemical and isotopic composition of 26 soil gas wells and 11 springs along the active fault zones in the capital area of China was determined to investigate the origin of CO2, the spatial and temporal variations of CO2 emission, and their mechanisms. The chemical and isotopic data indicated that biogenic CO2 was the primary source for CO2 from the soil gas wells in both the basin and orogen regions, the crust-derived and mantle-derived CO2 could have ascended through the deep-cut faults and got into the springs, with a few diffusing into the soil gas wells. Minor air could have intruded into the soil gas wells in the orogen region through the faults cutting the surface, owing to the barometric pressure fluctuation. Relatively high He concentration, CO2 concentration, and flux of soil gas from wells were observed in the basin region than those in the orogen region. A significant amount of CO2 is produced during the process of oxidation of organic matter in the basin, where the organic matter accumulates in thick clayey strata. Further amounts of CO2 are produced by interactions between groundwaters and carbonates, which are widely represented in the basin region and by intruded air into the soil gas wells in the orogen region due to barometric pressure fluctuations. Temporal variations of CO2 concentration and CO2 flux were observed in soil gas wells in the basin region, where seismic activity is more frequent compared to those in the orogen, indicating that seismic activity could be responsible for the jumpily temporal variations of CO2 concentration and flux in wells. Monitoring activities of soil gas CO2 concentrations and CO2 fluxes in active fault zones should be carried out. Highlights: Origins of CO2 from the active fault zones were identified. Spatial and temporal variations of CO2 from the active fault zones were observed. Seismic activity could be responsible for CO2 degassing from active fault zones.